Perhitungan Volume Menggunakan autodesk Revit Pada Struktur Rumah Sakit Orthopedi dan traumatologi - Satrio Wibowo Amroin (Jurnal Vokasi Teknik Sipil, 2024)
The construction sector in Indonesia is currently experiencing rapid progress, in line with the adoption of increasingly advanced technology. This technology greatly assists in various aspects of construction projects, particularly in the planning and calculation of structural work volumes. One of the commonly used software for this purpose is Autodesk Revit. This research was conducted at the Orthopedic and Traumatology Hospital 3 project in Surabaya, with the aim of calculating the work volume of various structural elements, such as foundations, sloofs, columns, beams, stairs, slabs, and elevator walls, and then comparing the results with existing volume data. The method used is quantitative descriptive. The results of the calculations using Autodesk Revit showed work volumes such as 13.45 m³ for working floors, 300.16 m³ for foundations with 5021.76 kg of reinforcement, and 197.28 m³ for columns with 257.20 kg of reinforcement, as well as 75.36 m³ for shear walls with 4661.54 kg of reinforcement. There is a significant difference in volume calculations between the conventional method and the BIM software, with the shear wall showing the largest difference (46%) and the beam (26%).